2020
DOI: 10.17507/jltr.1102.25
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Collaborative Writing on EFL Learners’ Writing Skills and Their Perception of the Strategy

Abstract: This mixed-method study observes the effects of collaborative writing strategy on EFL learners’ writing skill and their perception of the strategy. The population consists of 80 students from a public senior high school in West Sumatra, Indonesia. The samples, which were selected by using cluster random sampling, were categorized as the experimental and control class. Each class were taught with different teaching strategies, experimental class was taught by using collaborative writing strategy and the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 7 publications
6
22
0
Order By: Relevance
“…This model improves their understanding of the learning material concept. It is in line with the results of a study conducted by Anggraini, Rozimela & Anwar (2020) about EFL students' perceptions of collaborative writing strategies. Although there is a slight difference in focus, in principle, it has the same substance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This model improves their understanding of the learning material concept. It is in line with the results of a study conducted by Anggraini, Rozimela & Anwar (2020) about EFL students' perceptions of collaborative writing strategies. Although there is a slight difference in focus, in principle, it has the same substance.…”
Section: Discussionsupporting
confidence: 89%
“…To date, there have been several studies that have focused on students' perceptions of collaborative writing models. For example, research conducted by Anggraini, Rozimela & Anwar (2020) describes how EFL students' perceptions of collaborative writing strategies. The findings of this study indicate that students have positive perceptions of several significant elements in collaborative writing strategies such as understanding topics, feedback, and simultaneously increasing vocabulary mastery.…”
Section: Concept Of Perceptionmentioning
confidence: 99%
“…Research has indicated the varying degrees of the effects and students' perceptions of collaborative writing in their learning process. These positive sides are evidenced in Malaysia (Fung, 2006), the United States (Bikowski & Vithanage, 2016), Indonesia (Anggraini et al, 2020), in China (Zhang, 2018) , Saudi Arabia (Alawaji, 2020), in Spain (Dobao & Blum, 2013;Villarreal & Gil-Sarratea, 2020), and in Vietnam (Pham, 2021). In other words, the findings from these studies reveal that collaborative writing is a useful strategy that offers students the opportunity to pool ideas, improve writing quality regarding content, organization, and vocabulary.…”
Section: Collaborative Writingmentioning
confidence: 95%
“…Collaborative writing has taken its place in providing students with an opportunity to better their writing and language use and through working together to produce a given assignment (McDonough, Vleeschauwer, & Crawford, 2019;Storch, 2005Storch, , 2013. These studies into this area have shown potential benefits of promoting students' learning process for a quality written project with particular regard to content, vocabulary, and accuracy (Anggraini, Rozimela, & Anwar, 2020). This productive skill allows students to become proficient in using the target language, namely English and optimize their writing products, thereby influencing how students communicate their ideas to academic audiences or peers in clear and meaningful ways and facilitate their English language learning.…”
Section: Introductionmentioning
confidence: 99%
“…Online collaborative writing (OCW), as one of the computer‐supported collaborative learning modes, has been increasingly used in the higher education contexts (Anggraini et al, 2020; Liao et al, 2018; Pham, 2021). In an OCW activity, students collaboratively write in small groups or pairs via online platforms with the supports of instructional scaffoldings or technological assistances (Fan & Xu, 2020; Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%